Downregulation of IL-18 Expression in the Gut by Metformin-induced Gut Microbiota Modulation - Lee, Heetae (Immune Netw, 2019)
IL-18 is a crucial pro-inflammatory cytokine that mediates chronic intestinal inflammation. Metformin, an anti-diabetic drug, was reported to have ameliorative effects on inflammatory bowel disease. Recently, the mechanism of action of metformin was explained as a modulation of gut microbiota. In this study, fecal microbiota transplantation (FMT) using fecal material from metformin-treated mice was found to upregulate the expression of GLP-1 and pattern-recognition receptors TLR1 and TLR4 for the improvement in hyperglycemia caused by a high-fat diet. Further, FMT downregulated the expression of the inflammatory cytokine IL-18. Within the genera Akkermansia, Bacteroides, and Butyricimonas, which were promoted by metformin therapy, Butyricimonas was found to be consistently abundant following FMT. Our findings suggest that modulation of gut microbiota is a key factor for the anti-inflammatory effects of metformin which is used for the treatment of hyperglycemia.